2022
DOI: 10.1002/pro.4491
|View full text |Cite
|
Sign up to set email alerts
|

A backbone‐dependent rotamer library with high (ϕ, ψ) coverage using metadynamics simulations

Abstract: Backbone‐dependent rotamer libraries are commonly used to assign the side chain dihedral angles of amino acids when modeling protein structures. Most rotamer libraries are created by curating protein crystal structure data and using various methods to extrapolate the existing data to cover all possible backbone conformations. However, these rotamer libraries may not be suitable for modeling the structures of cyclic peptides and other constrained peptides because these molecules frequently sample backbone confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Analyses of coil libraries and MD simulations have clearly revealed that different amino acid side chains differ in terms of the population of these rotamers and that these populations depends on the backbone conformation. 155,[174][175][176][177] Experimental work exploring the rotamer populations of residues in short peptide is practically non existing. The only exception I am aware of is the paper of Rybka et al, who measured 3 J(H Ca H Cb ) coupling constant of the two C b -protons to determine the rotamer distributions of GNG, protonated and ionized GDG and of the protonated blocked tetrapeptide Ac-GDG.…”
Section: Structural Heterogeneity Of Side Chainsmentioning
confidence: 99%
“…Analyses of coil libraries and MD simulations have clearly revealed that different amino acid side chains differ in terms of the population of these rotamers and that these populations depends on the backbone conformation. 155,[174][175][176][177] Experimental work exploring the rotamer populations of residues in short peptide is practically non existing. The only exception I am aware of is the paper of Rybka et al, who measured 3 J(H Ca H Cb ) coupling constant of the two C b -protons to determine the rotamer distributions of GNG, protonated and ionized GDG and of the protonated blocked tetrapeptide Ac-GDG.…”
Section: Structural Heterogeneity Of Side Chainsmentioning
confidence: 99%